Tahlilu Syakhshiyati as-Syakhshi ar-Raisii fi Hikayati al-Arwah Al-Mutamarridah li Gibran Khalil Gibran - Riski Gunawan; Mohammad Zainal Hamdy; Uswatun Hasanah (Arabic Literature Department STIBA DUBA PAMEKASAN, 2021)
Personality is very influential on individual behavior, especially in social matters and in solving life's problems. Every individual has a different personality. The personality of each individual can be influenced by the sharing of factors that give rise to social phenomena in interacting with others every day. This research is a qualitative descriptive study with a type of librariy research. The data collection technique uses documentation techniques which are included in the technique or reading and recording. This type of research. The data collection’s technique is done by reading, translation, and taking. The data analysis technique is that using….. The results of this study are: 1) who personalitiy’s structure of the main character in Al- Arwah Al- Mutamarridah. 2) what cause of personality’s type in Al- Arwah Al- Mutamarridah.